The Influence of Principal's Leadership, Supervision, and Work Motivation on Teacher Professionalism at Yadika High School Cicalengka Bandung Regency - Froilan Delute Mobo; Tera Lesmana (Eastasouth Institute, 2022)
In education child age early, formal education, school basic and education intermediate, task teacher's main educate, teach, guide, direct, train, and evaluate students. Title education is held by the teacher. because of that, the progressive community, and the growth of personal students depend on educator professionals. To write a paper, on the technique study quantitative used. Studies this focus on how to control administrative, incentive work, and leadership influence teacher professionalism. At Yadika High School Cicalengka Bandung Regency , investigation done . Debate leads to deduction following: Every claim influences teacher professionalism: Leadership, supervision, and motivation work everything impact. This thing supported by a statement as follows: 1) Leadership impact Positive and Significant; 2) Supervision impact Positive and Significant ; 3) Motivation Work impact Positive and Significant. If Yadika High School Cicalengka Bandung Regency means to increase teacher professionalism, then must be capable increase leadership, supervision, and motivation work. We will make recommendations and suggestions for school this to related parties.